PROSPECTS OF USING TORSION PENDULUMS TO DETECT NEAR-EARTH DARK MATTER - Хомин, Богдана; Чурсанова, Марина; Дрозденко, Олександра (SWorldJournal, 2025)
This paper presents a review of a promising experimental technique for the direct detection of ultralight vector dark matter, which remains one of the least studied forms of this hypothetical substance. The central theme is the use of a differential tors